2020
DOI: 10.1016/j.wneu.2020.01.136
|View full text |Cite
|
Sign up to set email alerts
|

Large Difference Between Proximal Junctional Angle and Rod Contouring Angle is a Risk Factor for Proximal Junctional Kyphosis

Abstract: Background: There are several risk factors for proximal junctional kyphosis (PJK) in adolescent idiopathic scoliosis (AIS) surgery. Decreased rod contouring angle (RCA) has been proposed as a risk factor for PJK, but the role of difference between proximal junctional angle (PJA) and RCA (PJA-RCA) has not been fully investigated. The aim of this study was to assess the role of PJA-RCA for the development of postoperative PJK in AIS. Methods: We performed a retrospective analysis of 96 AIS patients who underwent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 20 publications
3
24
3
Order By: Relevance
“…[2][3][4][5][6] A plethora of literature exists on the clinical and radiographic risk factors for PJK. 3,[7][8][9][10][11][12][13][14][15][16][17][18] However, prevention of PJK remains unsolved and is still a relatively common postoperative complication.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6] A plethora of literature exists on the clinical and radiographic risk factors for PJK. 3,[7][8][9][10][11][12][13][14][15][16][17][18] However, prevention of PJK remains unsolved and is still a relatively common postoperative complication.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the definition employed in previous studies, the incidence of PJK varies between 14% and 46 %. [4][5][6][7][8][9][10][11] The big variation in literature comes from having studies analyzing different types of scoliosis, such as AIS, neuromuscular or adult spinal deformities. Different and more risk factors have been identified in adults and patients with neuromuscular scoliosis than in patients with idiopathic scoliosis.…”
Section: Discussionmentioning
confidence: 99%
“…[2,3] One of the currently most discussed problems is Proximal Junctional Kyphosis (PJK), a radiological finding that can manifest itself in the clinical problem of Proximal Junctional Failure. Depending on the used definition of PJK the incidence varies between 14 and 46 % [4][5][6][7][8][9][10][11] with a revision rate of about 10%. [12] The etiology of PJK seems to be multifactorial and has not yet been conclusively clarified.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yan [ 16 ] demonstrated that mismatch between postoperative PJA and PRCA led to a proximal compensation, namely PJK in degenerative scoliosis. After reviewing 84 adolescent idiopathic scoliosis patients, Wang et al [ 24 ] found that larger postoperative PJA-PRCA, especially those with PJA-PRCA greater than 5° were risk factors for PJK.…”
Section: Discussionmentioning
confidence: 99%